Sur la difference entre dire et connaitre le vrai: en defense du realisme metaphysique - Longo, Anna (Scenari, 2021)
This paper focuses on the difference between anti-metaphysical and metaphysical realism as it has been introduced by Jocelyn Benoist’s L’addresse du Réel. I will demonstrate that the philosophical approach known as “speculative realism” is not, as it has been critically defined, a mere retourn to the dogmatism of the things-in-themselves, but a completely different project that aims to justify the objectivity of scientific knowledge. This does not entail the necessity of overcoming the limits of experience, but the necessity of knowing why some certain descriptions of experienced objects can be considered as objective, while other must be considered as true reports of subjective experience.